RELAVANSI KURIKULUM DAN PEMBELAJARAN DALAM PENDIDIKAN - Rahayu, Maya Sri; Hasan, Izhar; Asmendri, Asmendri; Sari, Milya (Dharmas Education Journal (DE_Journal), 2023)
Changes in the curriculum that often change from time to time affect the way learning in schools. The curriculum provides guidance for teachers to design learning activities in accordance with the needs and demands of the times. Curriculum changes are made to update or improve the quality of education. By updating subject matter or adding the latest content that is relevant to today’s times. Curriculum and learning are interrelated because the curriculum is a learning plan that includes objectives, content, methods and evaluations that will be carried out in the learning process. Learning is a process of interaction between educators and leaners that refers to predetermined goals in the curriculum. Learning involves the use of appropriate methods to facilitate the process of cognitive, psychomotor and affective acquisition in leaners. In this study using library research approach with techniques to analyze relevant literature or written information sources. Learning and curriculum change are interrelated. Good learning will help acquire the knowledge and skills that students want from curriculum and appropriate curriculum changes will help increase the effectiveness of classroom learning.